Медвежонок в малиновом лесу - Заболотная Этери Николаевна (Читаем сами, 2016)
Экземпляры: Ф22 (20170626) / Инвентарный номер: 54086 / Цена: 37.00 / Сис.шифр: Д / Авт.знак: З-12 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6